ANALYSIS OF THE PROFITABILITY OF ALBANIAN BANK USING TIME SERIES MODELS - Xhoxhi, Olsi (PEOPLE: International Journal of Social Sciences, 2024)
This research focuses on predicting the profitability of the Bank of Albania, specifically measured by Return on Assets (ROA), by employing advanced time series analysis techniques. ROA is a fundamental financial metric reflecting the bank's ability to efficiently utilize its assets to generate profit, and it holds crucial implications for the stability and sustainability of the central bank. In this research, we have obtained a monthly dataset regarding the profitability of Albanian banks (Roa), covering the period from January 2016 to March 2023. Following an extensive data analysis, we have determined that the SARIMAX(0, 0, 1)x(2, 0, [1, 2], 12) model is the most suitable option for modeling our dataset. The SARIMAX(0, 0, 1) element signifies a non-seasonal moving average component, addressing short-term fluctuations and irregularities in the data. The seasonal component, (2, 0, [1, 2], 12), takes into account both annual and semi-annual patterns, aligning with the observed seasonal trends in the data. The results are expected to be instrumental for policymakers, financial analysts, and stakeholders concerned with the Bank of Albania's financial health. By applying time series analysis to ROA prediction, this research not only aims to enhance the central bank's financial decision-making capabilities but also contributes to the broader understanding of financial stability within the context of Albania's economic landscape